Synthesis and Antimicrobial Activities of 1-substituted-3,5-diaryl Pyrazolines - S. Jamode, V.; D. V. Thakre, Miss. (Asian Journal of Chemistry, 2010)
Some new pyrazolines(4, 5) were synthesized and tested for antimicrobial activities against S. aureus. E. coli. Pro mirabilis and A. aerugenes.